National forest problems in Alaska [microform] : hearings before the Subcommittee on Environment, Soil Conservation, and Forestry of the Committee on Agriculture and Forestry, United States, Ninety-fourth Congress, second session . - United States. Congress. Senate. Committee on Agriculture and Forestry. Subcommittee on Environment, Soil Conservation, and Forestry. (Washington : U.S. Govt. Print. Off., 1976)
Reuse of record except for individual research requires license from Congressional Information Service, Inc. Hearings held in Juneau, Sitka, and Ketchikan, Alaska, Aug. 18-21, 1976. CIS Microfiche Accession Numbers: CIS 77 S161-2 Includes bibliographical references. Microfiche. Mode of access: Internet.